2012
DOI: 10.1124/dmd.112.045674
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: Immunohistochemical and Functional Characterization of Peptide, Organic Cation, Neutral and Basic Amino Acid, and Monocarboxylate Drug Transporters in Human Ocular Tissues

Abstract: Since there is paucity of information on solute transporters in human ocular tissues, the aim of this study was immunohistochemical and functional characterization of peptide transporters (PEPT), organic cation transporters (OCTs), neutral and basic amino acid transporters (ATB 0,+ ), and monocarboxylate transporters (MCTs) in human ocular barriers. Immunohistochemical localization of transporters was achieved using 5-mm-thick paraffin-embedded sections of whole human eyes. In vitro transport studies were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Our recent study in human ocular tissues showed the expression and activity of PEPT, OCT, ATB 0,+ , and MCT transporters in cornea as well as retinal pigmented epithelium (RPE) 62 . Although the mRNA expression is responsible for protein expression and activity, there are many instances in which mRNA levels show poor correlation with protein levels 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study in human ocular tissues showed the expression and activity of PEPT, OCT, ATB 0,+ , and MCT transporters in cornea as well as retinal pigmented epithelium (RPE) 62 . Although the mRNA expression is responsible for protein expression and activity, there are many instances in which mRNA levels show poor correlation with protein levels 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Peptide transporters have been reported to be highly expressed on corneal epithelium (Anand and Mitra, 2002; Kadam et al, 2013; Xiang et al, 2009). These transporters can be targeted with prodrugs due to their broad substrate specificity, affinity and capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The structure, function, mechanisms and substrate specificity have been widely explored. Peptide transporters are highly expressed on cornea (Anand and Mitra, 2002; Kadam et al, 2013; Xiang et al, 2009). These transporters have been targeted to improve transcorneal absorption of poorly permeable drugs such as acyclovir (Anand et al, 2006; Anand and Mitra, 2002) and ganciclovir (Gunda et al, 2006; Majumdar et al, 2005) in our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to efflux pumps, peptide transporters are highly expressed on the apical surface of corneal epithelial cells (21)(22)(23). This influx transporter has been widely targeted to improve corneal drug absorption due to its high affinity, capacity, and broad substrate specificity.…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%
“…Peptide transporters have been widely targeted due to high substrate affinity, capacity, and broad specificity. These influx transporters have been demonstrated to be highly expressed on the apical surface of the corneal epithelium (21)(22)(23). This transporter has previously been targeted with amino acid and dipeptide prodrugs to improve corneal transport of poorly permeable drugs (23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%